An Ethnomathematical Analysis of the At-Taqwa Mosque Minaret, Cirebon: Implications of Mathematics Learning - Mauliddiyah Istiqomah; Intan Salsabila; Abirrotun Nabilah; Husni Muhammad Rayhan; Arif Muchyidin (Journal of Mathematics Instruction, Social Research and Opinion, 2026)
This research aims to address a research gap in the integration of mathematical concepts into Islamic architectural design by examining the tower of the At-Taqwa Mosque in Cirebon through an ethnomathematical lens. Using a descriptive qualitative approach, data is collected through field observations, visual documentation, and geometric shape analysis to identify the mathematical structures embedded in the mosque architecture. The results showed that the 65-meter-tall tower incorporates a variety of geometric elements, including a golden dome, a conical top, and an octagonal prism, symbolizing a spiritual ascent from the earthly to the divine. The octagonal shape serves as a transitional geometry between the square, representing the earth, and the circle, symbolizing the sky, reflecting the cosmological harmony in Islamic architecture. In addition, repetitive patterns such as squares, zig-zags, and rhombuses are closely related to cultural and religious values rooted in the Wali Songo tradition. The tower's vertical structure, which gradually narrows, can be modeled mathematically as a geometric sequence, symbolizing a spiritual elevation toward transcendence. Overall, architectural design embodies basic mathematical principles, including symmetry, tessellation, geometric transformation, and proportional reasoning. These findings suggest that integrating mosque architecture into mathematics instruction can increase cultural awareness, spatial reasoning skills, and appreciation for the interconnectedness among mathematics, art, and spirituality.